Reinsurance Trading in Lloyd’s of London: Balancing Conflicting-yet-Complementary Logics in Practice - Smets, Michael; Jarzabkowski, Paula; Burke, Gary T.; Spee, Paul (Academy of Management Journal, 2015)
Drawing on a yearlong ethnographic study of reinsurance trading in Lloyd’s of London, this paper makes three contributions to current discussions of institutional complexity. First, we shift focus away from structural and relatively static organizational responses to institutional complexity and identify three balancing mechanisms—segmenting, bridging, and demarcating—that allow individuals to manage competing logics and their shifting salience within their everyday work. Second, we integrate these mechanisms in a theoretical model that explains how individuals can continually keep coexisting logics, and their tendencies to either blend or disconnect, in a state of dynamic tension that renders them conflicting-yet-complementary logics. Our model shows how actors are able to dynamically balance coexisting logics, maintaining the distinction between them while also exploiting the benefits of their interdependence. Third, in contrast to most studies of newly formed hybrids and/or novel complexity, our focus on a long-standing context of institutional complexity shows how institutional complexity can itself become institutionalized and routinely enacted within everyday practice.